Design and Implementation of Digital Transmitter Monitoring Information System for TVRI East Java Transmission Unit Using Scrum Framework - Pratama, Ario Satria Wahyu; Shanty, Ratna Nur Tiara; Swastyastu, Cempaka Ananggadipa (Journal of Information Technology and Cyber Security, 2025)
The Digital Transmitter Monitoring Information System for the TVRI East Java Transmission Unit is developed to enhance efficiency in recording and monitoring transmitter conditions, which were previously documented manually using logbooks. This system is designed to facilitate operators in recording technical transmitter data and assist technicians in the failure analysis process. The development method used is the Scrum methodology, allowing the system to be developed iteratively with improvements based on user feedback. System testing is conducted using Black-Box Testing to ensure all features function according to user requirements, while system acceptance evaluation is carried out using the Technology Acceptance Model (TAM) to measure the system's usability and ease of use. The testing results indicate that all system features function properly without significant errors. The TAM evaluation produced an average score of 84.5% for perceived usefulness and 86.5% for perceived ease of use, indicating that the system is well accepted by users. With key features such as transmitter data recording, reporting, employee performance tracking, and data export, this system is expected to help TVRI East Java monitor digital transmitters more effectively and efficiently. Compared to the previous manual logbook system, this digital-based approach reduces dependency on physical documentation, minimizes the risk of data loss, and improves accessibility for operators and technicians. By enabling centralized data storage and streamlined reporting, the system ensures that monitoring activities are more structured, responsive, and cost-effective.